Should we speak of “a principle of harmony in general” in Leibniz? - Lalanne, Arnaud (ARFIL y UNL, 2020)
My purpose is to show that the general notion of harmony is transformed by Leibniz into a “principle”, and more specifically into a “principle of general harmony”. In the beginning, Leibniz establishes a distinction between the “harmonia universalis” and the “harmonia praestabilitata”, it means: between the general notion of harmony and his particular use in the mind-body problem. But in the last philosophy of Leibniz, appears a common denomination for the both harmonies as “principle of the general harmony”, in the sense of principle of the “divine wisdom”.